Work Hard, Party Hard: Harm Reduction in a Postsecondary Setting - Ford, Victoria; Wooster, Alyssa; Bartram, Mary (Canadian Journal of Higher Education, 2021)
In the context of the increasing focus on harms, psychological safety, and mental health in post-secondary settings, this qualitative study explores the challenges and opportunities for harm reduction through focus groups with student leaders, service providers, and administrators in one large Canadian university. Key themes explored by participants include a pervasive work hard, party culture, clashes regarding how to define and operationalize harm reduction, broad approaches to harm reduction in tension with the risk of becoming a band-aid solution, and knowledge transfer and privilege in an academic context. These findings suggest possible avenues for harm reduction that could be implemented as part of the new post-secondary standard, as well as in society as a whole.